Bosnia's Internal War and the International Criminal Tribunal - Hayden, Robert M. (Tufts Archival Research Center, 2005)
Volume 22, Issue 1. Winter/Spring The Bosnian conflict was not a matter of external aggression, but rather of the complete failure of the Bosnian state as it had been defined by its own constitutional structures.